THE IMPACT OF PROPHET MUHAMMAD’S (PBUH) TRADE ON ETHICAL BUSINESS PRACTICES - Abbas Khan; Fazal Numan Khan (Policy Research Journal, 2025)
This study explores the ethical business practices exemplified by Prophet Muhammad (PBUH) and their relevance in contemporary trade. It identifies four key principles: honesty and transparency, fair treatment of customers and partners, trust and integrity,and accountability and justice. The purpose of the study is to examine how these principles can inform modern business ethics and provide a moral framework for sustainable and fair trade. The research methodology involves a qualitative analysis of historical texts, including Hadiths and biographical accounts, to extract ethical teachings relevant to trade practices. Additionally, contemporary case studies of businesses inspired by Islamic principles are analyzed to illustrate practical applications of these teachings. The findings highlight the enduring significance of Prophet Muhammad’s (PBUH) ethical standards in addressing current challenges such as corruption and exploitation in business. The study concludes that adopting these principles can enhance corporate social responsibility and foster trust in commercial relationships. Recommendations include incorporating ethical training based on these principles into corporate strategies, developing supportive policy frameworks, and promoting research on Islamic business ethics in academia. By embracing these values, businesses can contribute to a more equitable and sustainable global economy.